Bifunctional monomer oligomers-based composite molecularly imprinted membranes for the electrochemical monitoring of Sudan I. Issue 16 (20th July 2022) - Gao, Qing; Zang, Yang; Xie, Ju; Chen, Lanfen; Xu, Jiaqi; Huang, Hao; Xue, Huaiguo
Abstract : P(L)ICO and PASCO-independent bifunctional monomer oligomers were utilized to construct a molecularly imprinted electrochemical sensor for monitoring Sudan I. Abstract : Herein, we developed a highly sensitive electrochemical sensor for the trace detection of Sudan I (SDI) dye based on composite molecularly imprinted membranes (MIMs). The pentenyl (lipoic acyl)-isoleucyl-chitosan oligosaccharide (P(L)ICO) and pentenyl-asparaginyl-chitosan oligosaccharide (PASCO) served as bifunctional monomer oligomers. After deposition of gold nanoparticles on a glassy carbon electrode (GCE) surface, a P(L)ICO layer successfully self-assembled on the surface. Subsequently, the primary MIM was polymerised on the electrode surface by using SDI as a template, PASCO as a functional monomer oligomer, and ethylene glycol dimethacrylate as a cross-linking agent. Electrochemical polymerisation was then conducted in an N, N ′-methylenebisacrylamide solution. After eluting the SDI molecules from the composite MIMs, the fabricated SDI-MIM(PM)/Fn-Au/GCE demonstrated specific adsorption of SDI. Under optimal conditions, the constructed sensor exhibited a linear relationship between decreasing peak current and SDI concentration from 0.02 to 3.5 μM with a low detection limit of 4 nM (S/N = 3). As a proof of concept, SDI-MIM(PM)/Fn-Au/GCE was also applied to detect SDI in chili powder samples, with recoveries ranging from 96.8 to 106.6%.